Curcumin Improves Cardiopulmonary Resuscitation Outcomes by Modulating Mitochondrial Metabolism and Apoptosis in a Rat Model of Cardiac Arrest - Zhang, Jie; Liu, Siqi; Jiang, Longyuan; Hou, Jingying; Yang, Zhengfei (Frontiers in Cardiovascular Medicine, 2022)
Background Curcumin, a diarylheptanoid chemical compound extracted from curcuma longa, exerts a variety of biological and pharmacological effects in numerous pathological conditions, including ischemia/reperfusion (I/R) injury. In this study, we investigated its role in post-resuscitation myocardial dysfunction in a rat model of cardiac arrest (CA) and cardiopulmonary resuscitation (CPR) by targeting on mitochondrial metabolism and apoptosis. Methods Animals were randomized into three groups: sham, control and curcumin, with fifteen rats in each group. Ventricular fibrillation (VF) was induced in the rats of the control and curcumin groups. The rats in the two groups were untreated for 8 min, followed by CPR for 8 min. Placebo (saline) or curcumin was administered by intraperitoneal injection, respectively, 5 min after successful resuscitation. Myocardial function was measured at baseline and post-resuscitation for 6 h consecutively. Ten rats in each group were closely observed for an additional 66 h to analyze the survival status, and the remaining five were sacrificed for the measurement of mitochondrial parameters and cell apoptosis. Results Compared with the control group, myocardial function was significantly enhanced in the curcumin group, contributing to a better survival status. Curcumin treatment mitigated the depletion of superoxide dismutase (SOD) and the production of malondialdehyde (MDA). The structural damage of mitochondria was also alleviated, with improved conditions of mPTP and ΔΨm. Curcumin boosted the production of ATP and attenuated myocardial apoptosis. Cytochrome C, caspase-3 and its cleavage were suppressed by curcumin. Proteins closely related to the functional performance of mitochondria, including uncoupling protein 2 (UCP2) and uncoupling protein 3 (UCP3) were downregulated, while mitochondrial transcription factor A (mtTFA) was upregulated. Conclusion Curcumin improves the outcomes of CPR via alleviating myocardial dysfunction induced by I/R injury. It exhibits anti-oxidation properties. Moreover, it is capable of ameliorating mitochondrial structure and energy metabolism, as well as inhibiting the mitochondrial apoptosis pathway. UCP2, UCP3, and mtTFA might also be involved in curcumin mediated protective effects on mitochondria.